Leucocyte expression of complement C5a receptors exacerbates infarct size after myocardial reperfusion injury. (15th June 2014) - De Hoog, Vince C.; Timmers, Leo; Van Duijvenvoorde, Amerik; De Jager, Saskia C. A.; Van Middelaar, Ben J.; Smeets, Mirjam B.; Woodruff, Trent M.; Doevendans, Pieter A.; Pasterkamp, Gerard; Hack, C. Erik; De Kleijn, Dominique P.V.
Abstract: Aims: Early reperfusion is mandatory for the treatment of acute myocardial infarction. This process, however, also induces additional loss of viable myocardium, called ischaemia–reperfusion (IR) injury. Complement activation plays an important role in IR injury, partly through binding of C5a to its major receptor (C5aR). We investigated the role of C5aR on infarct size and cardiac function in a model for myocardial IR injury. Methods and results: BALB/c (WT) mice and C5aR −/− mice underwent coronary occlusion for 30 min, followed by reperfusion. Infarct size, determined 24 h after IR, was reduced in C5aR −/− mice compared with WT mice (28.5 ± 2.1 vs. 35.7 ± 2.5%, P = 0.017). Bone marrow (BM) chimaera experiments showed that this effect was due to the absence of C5aR on circulating leucocytes, since a similar reduction in infarct size was observed in WT mice with C5aR-deficient BM cells (25.3 ± 2.2 vs. 34.6 ± 2.8%, P < 0.05), but not in C5aR −/− mice with WT BM cells. Reduced infarct size was associated with fewer neutrophils, T cells, and macrophages in the infarcted area 24 h after IR in C5aR −/− mice, and also with lower levels of Caspase-3/7 indicating less inflammation and apoptosis. Echocardiography 4 weeks after IR showed an improved ejection fraction in C5aR −/− mice (25.8 ± 5.5 vs. 19.2 ± 5.4%, P < 0.001). Conclusion: The absence of C5aR on circulating leucocytes reduces infarct size, is associated with reduced leucocyte infiltration and with less apoptosis in the infarcted myocardium, and improves cardiac function in a mouse model of myocardial IR injury. Selective blocking of C5aR might be a promising strategy to prevent myocardial IR injury.